Quinine, the symbol of the XXII Ibero-American Chemistry Olympiad-2017 - Nakamatsu, Javier (2019)
Quinine, present in the bark of the cinchona tree, native to the South American Andes, is one of the natural medicines that has saved more lives in the history of humanity. Its economic importance, as a treatment for malaria, generated a search for its synthetic route. This promoted the development of organic synthesis and marked the beginning of industrial organic chemistry. Quinine, a compound so connected not only with the history of Peru but also with that of organic synthesis, was highlighted in the XXII Ibero-American Chemistry Olympiad-2017.